Characteristics of Flakes from Kepok Banana Flour and Black Rice Flour with Variation of Steaming Time - Rachmawati, Shinta Dwi; Yulistiani, Ratna; Jariyah, Jariyah (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
This research has the objective of determining the effect of flour rasio kepok banana and black rice. Black rice flour with variations in steaming time on physicochemical characteristics of flakes. This research used a randomized Complete Design (RCD) factorial pattern with two factors and two replications. The first factor is thr proportion of kepok banana flour: black rice flour (30%: 70%, 40%: 60%, and 50%:50%) and the second factor is the length of steaming time (10 minutes, 15 minutes, 20 minutes). The data obtained was analyzed using ANOVA and followed by the Duncan Multiple Range Test (DMRT) at the 5% level. The results of the research showed that there was interaction. There was a significant difference between the treatments of kepok banana flour: black rice flour on moisture content, starch content, and water absorption. The best treatment is Banana flour: black rice flour on moisture content, starch content, and water absorption. The best treatment is flaked with a proportion of 50% kepok banana flour and 50% black rice flour and a steaming time of 10 minutes produced flakes with characteristics of the value of water content of 4.77%, ash content of 2.12%, fat content of 8.35%, content protein of 5.56%, the starch content of 78.01%, water absorption of 24.96%, hardness of 414.57N and dietary Fiber content of 5.22 %, the calcium content of 169.89mg/100g and the average of favorability scores for taste (3.83), color (4.80), aroma (4.20) and textire (3.37)